¿RESTOS DEL CÓDICE VISIGÓTICO MÁS ANTIGUO DE ORIGEN ARAGONÉS?: UNOS MORALIA IN IOB DE SAN GREGORIO DE LA PRIMERA MITAD DEL SIGLO IX IDENTIFICADOS EN JACA: REMAINS OF THE EARLIEST VISIGOTHIC MANUSCRIPT PRODUCED IN ARAGON ?: ONES GREGORY’S MORALIA IN IOB FROM THE FIRST HALF OF THE 9TH CENTURY RECENTLY DISCOVERED IN JACA - Alturo i Perucho, Jesús (Aragón en la Edad Media, 2025)
Identificación en el Archivo de la Catedral de Jaca de medio folio de un códice que transmite los Moralia in Iob de san gregorio en escritura visigótica de la primera mitad del siglo IX. su análisis codicográfico y paleográfico, presentación de variantes textuales y contextualización histórico-cultural permiten deducir un posible origen aragonés de la copia, en cuyo caso sería el códice más antiguo conocido de los producidos en Aragón en escritura visigótica.Palabras clave: Moralia in Iob, grego- rio Magno, Escritura visigótica, Catedral de Jaca, Aragón.This study covers the identi- fication of one half of a folio recently discovered at Jaca’s Cathedral as a part of a manuscript that transmits gregory’s Moralia in Iob in visigothic writing from the first half of the 9th century. The codicographic and paleographic features, the textual variants and the historical and cultural context is central to afirm the possible Aragonese origin of this copy which could be the earliest known codex surviving today in visigothic writing, produced in Aragon.Keywords: Moralia in Iob, gregory the great, visigothic writing, Jaca’s Cathedral, Aragon.